The influence of rigid gas permeable lens wear on the concentrations of dinucleotides in tears and the effect on dry eye signs and symptoms in keratoconus - Carracedo, Gonzalo; González-Méijome, José Manuel; Martín-Gil, Alba; Carballo, Jesús; Pintor, Jesús (Contact lens & anterior eye, 2016)
•Ap4A, Ap5A and dry eye symptoms increase in keratoconus vs. healthy subjects.•RGP wearing exacerbates the signs and symptoms of dry eye in keratoconus patients.•RGP lens wear increases the Ap4A concentration in the tears of keratoconus patients. To evaluate the signs and symptoms of dry eye and dinucleotide secretion in tears of keratoconus patients (KC) and the potential effect of rigid gas permeable (RGP) contact lens wear. Twenty-three KC patients and forty control subjects were enrolled in this study. Signs of dry eye including tear volume, tear stability and corneal staining along with symptoms were assessed using the McMonnies questionnaire. Tears were collected using Schirmer strips, and dinucleotide concentrations in collected tears measured using high pressure liquid chromatography. Values obtained in KC and controls were compared. The effect of contact lens wear in KC was also assessed. KC eyes showed a significantly lower tear volume compared to controls, shorter tear break up time (TBUT), higher corneal staining and higher McMonnies dry eye questionnaire scores (p<0.05). When compared with non-wearers, KC contact lens wearers showed significantly higher symptoms, lower Schirmer and TBUT values (p<0.05). Concentration of Ap4A (0.695±0.304μM vs. 0.185±0.178μM) and Ap5A (0.132±0.128μM vs. 0.045±0.036μM) were higher in KC compared to controls (p<0.001) and only Ap4A was statistically higher in RGP wearers compared to non-wearers (0.794±0.478μM vs. 0.417±0.313μM) (p<0.05). Signs and symptoms of dry eye as well as concentrations of Ap4A and Ap5A were markedly increased in KC patients compared to controls. Moreover, Ap4A and symptoms of dry eye were statistically higher in RGP wearers compared to non-wearers. This seems to indicate that factors such as RGP contact lens wear might exacerbate the clinical condition of dry eye.